Quality of life levels in brazilian elite female college volleyball players - Correia, R. F.; Ribeiro, A. N.; Barbieri, J. F.; Brasil, D.; Motta, L.; Castaño, L. A. A.; Salve, M. G. C. (International Journal of Sports Science, 2017)
This article investigated quality of life levels and indicators in Brazilian elite female college volleyball players. Thirty-two athletes participated in this cross-sectional - survey type study, by answering two protocols: the WHOQOL-BREF and an academic-sports questionnaire developed by the authors. The athletes displayed high quality of life, showing results higher than the normative data presented for a random Brazilian female population in all its domains, except for the environment domain. The athletes showed discontent with the organization of university sports in Brazil, especially in relation to its schedule planning, which always conflicted academic and sportive activities, thus hindering both their training and academic formation. It is expected that this research will contribute to the continuing advancement of the investigations of the relationships between the practices of high-performance sports, be it collegiate or professional, and quality of life.